Evaluating Data Mining Classification Methods Performance in Internet of Things Applications - Sulaiman, Maryam Ameen (Journal of Soft Computing and Data Mining, 2020)
The world is passing through the stage of the superiority of science and technology. The impact of this superiority in human life cannot be hidden. There is no doubt that the societies that have acquired information and knowledge are now the ones who rule the world and lead the scene of developed and modern countries. With the development of advanced applications of the concept of the Internet of Things (IOT) in addition to the development of information and communication technologies, it can be used in public life, since IOT technologies have the ability to link physical entities and support interaction with the human element. The data that are generated by IoT is huge data that has a high commercial value also mining of data algorithms can be applied on the IOT to getting the hid data. In this paper, a systematic method is presented to a review the extraction of defined data classification. The latest algorithms of classification must be analyzed to apply on the big data. These algorithms are reviewed and the challenges you will face are discussed.